Mind your SMSes: Mitigating social engineering in second factor authentication. Issue 65 (March 2017) - Siadati, Hossein; Nguyen, Toan; Gupta, Payas; Jakobsson, Markus; Memon, Nasir
Abstract: SMS-based second factor authentication is a cornerstone for many service providers, ranging from email service providers and social networks to financial institutions and online marketplaces. Attackers have not been slow to capitalize on the vulnerabilities of this mechanism by using social engineering techniques to coerce users to forward authentication codes. We demonstrate one social engineering attack for which we experimentally obtained a 50% success rate against Google's SMS-based authentication. At the heart of the problem is the messaging associated with the authentication code, and how this must not have been developed with security against social engineering in mind. Pursuing a top-down methodology, we generate alternative messages and experimentally test these against an array of social engineering attempts. Our most robust messaging approach reduces the success of the most effective social engineering attack to 8%, or a sixth of its success against Google's standard second factor verification code messages.